2011
DOI: 10.3390/polym3010330
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Initial Substrate Concentration of the Belouzov-Zhabotinsky Reaction on Transmittance Self-Oscillation for a Nonthermoresponsive Polymer Chain

Abstract: We succeeded in causing transmittance self-oscillations of a novel self-oscillating polymer chain induced by the Belouzov-Zhabotinsky (BZ) reaction under constant conditions. The novel polymer chain was composed of a biocompatible and non-thermoresponsive poly-vinylpyrrolidone (PVP) main-chain, covalently-bonded to the ruthenium catalyst (Ru(bpy) 3 ) of the BZ reaction. We investigated the influence of initial substrate concentrations of the three BZ substrates on the transmittance self-oscillation of the nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 25 publications
0
22
0
Order By: Relevance
“…Thus, we can control the self-oscillating behavior by selecting an appropriate molecular structure of the polymer main chain. Figure 7 shows that all the logarithmic plots of the period of the self-oscillation of the VP-based polymer as a function of the initial molar concentration of one BZ substrate chain show good linear relationships [49]. Therefore, the period [T(s)] of the self-oscillation can be expressed as a [substrate] b where a and b are experimental constants and brackets denote the initial concentration.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Thus, we can control the self-oscillating behavior by selecting an appropriate molecular structure of the polymer main chain. Figure 7 shows that all the logarithmic plots of the period of the self-oscillation of the VP-based polymer as a function of the initial molar concentration of one BZ substrate chain show good linear relationships [49]. Therefore, the period [T(s)] of the self-oscillation can be expressed as a [substrate] b where a and b are experimental constants and brackets denote the initial concentration.…”
Section: Resultsmentioning
confidence: 93%
“…It was demonstrated that there was no LCST for the VP-based polymer chain in the reduced and oxidized states (see Figure 4) [49]. The solubility of the VP-based polymer chains was different in the reduced and oxidized states, as evidenced by the different transmittance values.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…The polymer chain is driven while consuming malonic acid, the energy source of the BZ reaction. This occurs because self-oscillating behavior is induced by a BZ reaction originating from the Ru(bpy)3 moiety in the polymer chain [13][14][15][16][17][18][19][20][21][22]. The BZ reaction has been much investigated and is a well-known oscillating reaction that causes spontaneous redox oscillation and a wide variety of nonlinear phenomena.…”
Section: Introductionmentioning
confidence: 99%